1998
DOI: 10.1159/000020522
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus Gene Transfer into Renal Cells: Potential for in vivo Gene Delivery

Abstract: The human parvovirus adeno-associated virus (AAV), type 2, has a number of features that make it an attractive choice as a vector for gene delivery to the kidney. AAV vectors permit long-term gene expression in vivo by integration into the host genome, have potential for site-specific integration on chromosome 19, do not express viral genes or generate a cellular immune response, and demonstrate enhancement of gene expression by chemotherapeutic agents that are approved for use in vivo. These properties confer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…It was demonstrated that delivery via renal artery perfusion resulted in gene expression predominantly in the renal cortex; in comparison, retrograde infusion via the ureter resulted in strong expression mainly in papillary tubular cells. [41][42][43] Recently, Gusella et al 44 studied the transduction of kidney in mice after delivery of lentiviral vectors by various routes of administration. After parenchymal or ureteral infusion, expression of the transgene was localized to the outer medulla and corticomedullary junction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was demonstrated that delivery via renal artery perfusion resulted in gene expression predominantly in the renal cortex; in comparison, retrograde infusion via the ureter resulted in strong expression mainly in papillary tubular cells. [41][42][43] Recently, Gusella et al 44 studied the transduction of kidney in mice after delivery of lentiviral vectors by various routes of administration. After parenchymal or ureteral infusion, expression of the transgene was localized to the outer medulla and corticomedullary junction.…”
Section: Discussionmentioning
confidence: 99%
“…Retroviral vectors direct gene expression predominantly in the outer medulla, 40 while adenoviruses could direct gene expression in either the outer medulla or inner medulla through different injection routes. [41][42][43] Renal arterial perfusion generated highest gene expression mainly in the outer medulla, while the highest gene expression is usually found in the papilla through retrograde infusion via the ureter. [41][42][43] In contrast, nonviral vectors consistently produce high gene expression either in the cortex or in the outer medulla and almost no expression could be detected in the inner medulla.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, besides being difficulty to be purified, endostatin has a short half-life in vivo. In order to circumvent the obstacle presented by the pharmacokinetics of endostatin, delivery of the gene cassettes encoding endostatin has been attempted [11][12][13][14][15][16][17][18][19] . Recombinant adeno-associated virus (rAAV) vector is a good candidate for antiangiogenesis-based cancer gene therapy [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Although its site of integration is known, the recombinant adeno-associated virus looses this property. Even though expression is longer than with the adenovirus, there are some limitations with this vector system mainly because it is difficult to produce large quantities of the virus, and it has a limited capacity for inserting the transgene [40][41][42]. Finally, lentiviral vectors can infect nondividing cells with high efficiency and can be produced with high titer.…”
Section: Antisense Delivery Methodsmentioning
confidence: 99%